Europe-Wide Meta-Analysis of Borrelia burgdorferi Sensu Lato Prevalence in Questing Ixodes ricinus Ticks - Strnad, Martin; Hönig, Václav; Růžek, Daniel; Grubhoffer, Libor; Rego, Ryan O M (Applied and environmental microbiology, 2017)
Lyme borreliosis is the most common zoonotic disease transmitted by ticks in Europe and North America. Despite having multiple tick vectors, the causative agent, Borrelia burgdorferisensu lato, is vectored mainly by Ixodes ricinus in Europe. In the present study, we aimed to review and summarize the existing data published from 2010 to 2016 concerning the prevalence of B. burgdorferi sensu lato spirochetes in questing I. ricinus ticks. The primary focus was to evaluate the infection rate of these bacteria in ticks, accounting for tick stage, adult tick gender, region, and detection method, as well as to investigate any changes in prevalence over time. The data obtained were compared to the findings of a previous metastudy. The literature search identified data from 23 countries, with 115,028 ticks, in total, inspected for infection with B. burgdorferi sensu lato We showed that the infection rate was significantly higher in adults than in nymphs and in females than in males. We found significant differences between European regions, with the highest infection rates in Central Europe. The most common genospecies were B. afzelii and B. garinii, despite a negative correlation of their prevalence rates. No statistically significant differences were found among the prevalence rates determined by conventional PCR, nested PCR, and real-time PCR.IMPORTANCEBorrelia burgdorferisensu lato is a pathogenic bacterium whose clinical manifestations are associated with Lyme borreliosis. This vector-borne disease is a major public health concern in Europe and North America and may lead to severe arthritic, cardiovascular, and neurological complications if left untreated. Although pathogen prevalence is considered an important predictor of infection risk, solitary isolated data have only limited value. Here we provide summarized information about the prevalence of B. burgdorferi sensu lato spirochetes among host-seeking Ixodes ricinus ticks, the principal tick vector of borreliae in Europe. We compare the new results with previously published data in order to evaluate any changing trends in tick infection.
Keywords: Ixodes ricinus; genospecies; Zoonoses; Borrelia burgdorferi; lymeská nemoc; Male; klíště; Lyme Disease; Nymph; Europe; prevalence; zoonózy; Arachnid Vectors; tick; mužské pohlaví; Lyme borreliosis; Evropa; arachnida jako vektory; nymfa; Animals; lidé; Borrelia burgdorferi sensu lato; ženské pohlaví; Humans; zvířata; Prevalence; Ixodes; meta-analysis; Female; Lyme disease